Phototoxic versus photoprotective effects of tattoo pigments in reconstructed human skin models: In vitro phototoxicity testing of tattoo pigments: 3D versus 2D. (August 2021) - Hering, Henrik; Zoschke, Christian; König, Frank; Kühn, Markus; Luch, Andreas; Schreiver, Ines
Highlights: Pigment-loaded skin models were used for tattoo related phototoxicity testing. Phototoxic pigments shield underlying fibroblasts from UV radiation in 3D skin models. Results are compared to 2D phototoxicity of pigments. Localization of tattoo pigments in skin is pivotal for their net toxicity. Abstract: The increasing number of tattooed persons urges the development of reliable test systems to assess tattoo associated risks. The alarming prevalence of 60 % phototoxic reactions in tattoos ask for a more comprehensive investigation of phototoxic reactions in tattooed skin. Here, we aimed to compare the cellular responses of human skin cells to ultraviolet (UV)A and UVB irradiation in doses of short to intermitted sun exposure (3–48 J/cm² and 0.05–5 J/cm², respectively) in the presence of tattoo pigments. Therefore, we used fibroblast monolayer culture (2D), our recently developed three dimensional full-thickness skin model with dermal-located tattoo pigments (TatSFT ) and its dermal equivalents (TatSDE ) that lack keratinocytes. We tested the most frequently used tattoo pigments carbon black, titanium dioxide (TiO2 ) anatase and rutile as well as Pigment Orange (P.O.)13 in ranges from 0.067 to 2.7 ng/cell in 2D. For TatSDE and TatSFT, concentrations were 1.3 ng/cell for TiO2, 0.67 ng/cell for P.O.13 and 0.067 ng/cell for carbon black. We assessed cell viability and cytokine release in all systems, and cyclobutane pyrimidine dimer (CPD) formation in TatSFT . Phototoxicity of tattoo pigments was exclusively observed in 2D, where especially TiO2 anatase induced phototoxic effects in all concentrations (0.067–2.7 ng/cell). In contrast, fibroblasts were protected from UV irradiation in TatSDE by TiO2 and carbon black. Neither toxic nor protective effects were recorded in TatSFT . P.O.13 showed altered cytokine secretion in 2D (0.067–1.3 ng/cell) and TatSDE, despite the absence of significant effects on viability in all systems. All pigments reduced the number of CPDs in TatSFT compared to the pigment-free controls. In conclusion, our study shows that within a 3D arrangement, intradermal tattoo pigments may act photoprotective despite intrinsic phototoxic properties in 2D. Thus, dermal 3D equivalents should be considered to evaluate acute tattoo pigment toxicology.